Nervous system the neuron : the action potential ([Atlanta, Ga.] : Benjamin/Cummings, 2000)
Animation, sound, narration, and video clips are used to explain physiological concepts and processes of the nervous system of the human body
Author, Susan J. Mitchell
System requirements: Windows: 166 MHz Intel Pentium processor or greater Windows 95/98/NT4/2000, monitor capable of displaying 800 x 600 pixels, 32 MB or more of installed RAM, quad-speed CD-ROM; Macintosh: 120 MHz PowerPC, MAC OS 8.1 or later, monitor capable of displaying 800 x 600 pixels, 18 MB or more of available RAM, quad-speed CD-ROM
Keywords: Neurophysiology